2021
DOI: 10.3386/w28753
|View full text |Cite
|
Sign up to set email alerts
|

School Reopenings, Mobility, and COVID-19 Spread: Evidence from Texas

Abstract: This paper examines the effect of fall 2020 school reopenings in Texas on county-level COVID-19 cases and fatalities. Previous evidence suggests that schools can be reopened safely if community spread is low and public health guidelines are followed. However, in Texas, reopenings often occurred alongside high community spread and at near capacity, making it difficult to meet social distancing recommendations. Using event-study models and handcollected instruction modality and start dates for all school distric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 17 publications
2
21
2
2
Order By: Relevance
“…This paper provides additional evidence by focusing on the whole country and by investigating the impact of both school openings and closures, as they may have non-symmetric effects on infections. My results are in line with studies on the United States (Courtemanche et al 2021), but are in contrast with evidence from other European countries, e.g., Germany (Isphording, Lipfert, and Pestel 2021;von Bismarck-Osten, Borusyak, and Schonberg 2022), where school openings did not contribute to a higher viral transmission. Differences between Italy and Germany may be due to a variety of factors.…”
Section: Introductionsupporting
confidence: 87%
“…This paper provides additional evidence by focusing on the whole country and by investigating the impact of both school openings and closures, as they may have non-symmetric effects on infections. My results are in line with studies on the United States (Courtemanche et al 2021), but are in contrast with evidence from other European countries, e.g., Germany (Isphording, Lipfert, and Pestel 2021;von Bismarck-Osten, Borusyak, and Schonberg 2022), where school openings did not contribute to a higher viral transmission. Differences between Italy and Germany may be due to a variety of factors.…”
Section: Introductionsupporting
confidence: 87%
“…Careful contact tracing would be helpful in focusing on the latter, but is not widely available. Finally, we do not focus on possible community spread as a result of schools opening, which is a separate consideration and has been considered in other work (Courtemanche et al, 2021;Harris et al, 2021;Harell & Lieberman, 2021).…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 3 , 7 However, more recent analyses suggested that school closure might reduce transmission, perhaps by as much as 15%. 4 , 8 , 9 , 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…In the first waves of the pandemic, school closures, for example, were found to have relatively minor effects in various types of studies 2,3,7 . However, more recent analyses suggested that school closure might reduce transmission, perhaps by as much as 15% 4,8‐11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation